Practical operation of Fenton oxidation/efficient precipitation in fluoride wastewater treatment - SUN Longhai; WANG Wenfeng; CHEN Liang; HAN Feichao (Gongye shui chuli)
This study addressed the issue of unstable fluoride levels in the effluent caused by the susceptibility of the wastewater to biochemical oxidation in the sewage treatment plant of an organic fluorine chemical park. In order to enhance the stability of the effluent and to reduce the concentration of organic fluorine compounds in the wastewater. Fenton oxidation/efficient precipitation method was chosen to upgrade the sewage treatment plant. Preliminary trials indicated that the organic fluorine compounds in the influent of the sewage treatment plant could be oxidized by both Fenton oxidation and ozone oxidation methods, resulting in an average fluoride increase rates of 35.48% and 46.79%, respectively. Engineering practices demonstrated that wastewater containing organic fluorine compounds could be treated by the combination of Fenton oxidation/efficient precipitation method. After Fenton oxidation, the average increase rate of fluorides was 29.40%, and the two-stage efficient precipitation achieved fluoride removal rates of 29.98% and 17.97%, respectively. The concentration of fluoride in the treated effluent was less than 4.5 mg/L, to meet the requirements of the discharge standard. The operating cost of the sewage treatment increased by 1.95 yuan per ton of water.